ISLAM DAN BUDAYA KORUPSI DALAM KEBOHONGAN STATISTIKA - Fatati Nuryana (Institut Agama Islam Negeri Madura)
AbstractStatistics is often assumed with the data formed figure, the result of accounting, or others related with the data collection. Statistics is a tool believed to express a scientific truth.. Unfortunately, this tool is often misused to reach the individual purposes suitable with it is wanted. Statistics is done by any way, beginning from incorrect sample taking, manipulating the data to the solution taking which is not suitable with the real result that can be the first becoming corruption that is forbidden in Islam. This writing wants to analyze the kinds of lie statistics forms that can bring to the corruption action, its view and solution according to Islamic perspective.Kata-kata kunciIslam , korupsi, kebohongan statistika, manipulasi